PENGARUH WORK FROM HOME DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI LPPKSPS - Dewi Susilowati; Hery Sawiji; Winarno Winarno (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
The purpose of this study is to determine: 1) the effect of working from home on employee performance; 2) the effect of work environment on the employee performance; and 3) the effect of work from home and work environment simultaneously on employee perfomance at LPPKSPS. This study is a quantitative study with a survey method. The population in this study were all employees at LPPKSPS, 74 employees based on employee data 2020. The sampling technique used saturated sample. Final sample of this study amounted to 68 due to mutations and employee pensions. Data collection techniques use questionnaires, documentation, and archives. Data analysis technique using prerequisite test and multiple regression analysis. The results showed that: 1) there was significant effect on working from home on employee performance as evidenced by tvalue(2.790)> ttable(1.997); 2) there was significant effect of work environment on employee performance as evidenced by tvalue(2.761)>ttable(1.997); and 3) there was significant effect of working from home and work environment  simultaneously on employees as evidenced by Fvalue(11.227)>Ftable(3.14). The results of this study indicate the double meaning of  X1 and X2 toY by 23.4% and the remaining 76.6% the influenced by other variables not included in this study.